2013
DOI: 10.1021/jp407247y
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation in Colloidal Suspensions: Evaluation of the Role of Hydrodynamic Interactions by Means of Numerical Simulations

Abstract: Numerical simulations constitute a precious tool for understanding the role of key parameters influencing the colloidal arrangement in suspensions, which is crucial for many applications. The present paper investigates numerically the role of hydrodynamic interactions on the aggregation processes in colloidal suspensions. Three simulation techniques are used: Brownian dynamics without hydrodynamic interactions, Brownian dynamics including some of the hydrodynamic interactions, using the Yamakawa-Rotne-Prager t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 24 publications
(61 reference statements)
1
29
0
Order By: Relevance
“…Tanaka and Araki [14] have presented strong indications that HIs influence the transient gel formation of colloidal particles. Other works have shown that HIs lead to the formation of less compact clusters, suggesting that this effect might significantly alter the value of / c [16,17]. However, the studies in Refs.…”
Section: Introductionmentioning
confidence: 92%
“…Tanaka and Araki [14] have presented strong indications that HIs influence the transient gel formation of colloidal particles. Other works have shown that HIs lead to the formation of less compact clusters, suggesting that this effect might significantly alter the value of / c [16,17]. However, the studies in Refs.…”
Section: Introductionmentioning
confidence: 92%
“…First, the ignorance of HI in the BD simulations may affect the dynamics of the cluster growth and phase separation. Recently, the effect of HI on the kinetics of colloidal aggregation was investigated by comparing simulation results from BD without HI with those from stochastic rotation dynamics-molecular dynamics (SRD-MD) in which HI is properly included [45]. Tomilov et al performed simulations of colloidal aggregation, using small systems that contain 500 particles, at several volume fractions between 0.025 and 0.20 at T Ã ¼ 0:071.…”
Section: Equilibrium Properties Of a Large Clustermentioning
confidence: 99%
“…'Colloidal fluids' with short-range correlations between the particle positions and 'colloidal crystals' with longrange spatial order have both been studied extensively. Under carefully controlled conditions, colloidal systems show rich behavior in particle aggregation [1,2], phase separation [3], gel formation [4], and crystallization [5,6]. Fundamental problems such as kinetics of crystal nucleation, growth, ripening, and phase transitions can be investigated in great detail by using colloidal systems as model systems [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In denser suspensions, self-and relative particle diffusion are retarded by pair-hydrodynamic interactions [17,18], while collective diffusion is enhanced by many-body hydrodynamic interactions [17,19,20]. If the hydrodynamic interaction dominants, colloidal particles usually cluster into complex structures which are not of energetically optimized configurations [2]. When only simple routes are possible, slow sedimentation of colloidal suspensions [6] is traditionally a preferred method to grow colloidal crystals.…”
Section: Introductionmentioning
confidence: 99%